Environmental impact assessment of highways and expressways – legal and ecological conditions - Zębek, Elżbieta (Studia Iuridica Toruniensia, 2022)
Highways and expressways are road investments which contribute to socio- economic development but have a negative impact on the environment. Environmental impact assessments are the legal instrument that contributes to limiting this negative impact. The purpose of this article is to define the legal nature and essence of the environmental impact assessments of highways and expressways, and to define the role of this legal instrument in the protection of its resources. Environmental impact assessments are a legal instrument and placed in the procedure of obtaining a decision on environmental conditions, which is the first administrative decision in the implementation of projects with significant environmental impact, such as highways and expressways. However, the type of planned protection solutions depends on the degree of detail in determining the potential impact on individual elements of the environment, which is difficult in practice and is the reason for challenging the correctness of EIA reports. Moreover, there are no clearly defined requirements for road environmental protection devices.